CUSTOMER RELATIONSHIP MARKETING DI RAMAYANA DEPARTEMENT STORE PADA MASA PANDEMIC COVID-19 - Rahmawati, Nur Fitri; Toana, Rangga Dalu Aji; Sofyan, Mohammad (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2021)
he Covid 19 pandemic has hit the economy and business globally, one of which is the Ramayana Department Store where sales have decreased. It is necessary to have a customer relationship marketing strategy to maintain customer loyalty which leads to increased sales. The purpose of this study is to analyze the customer relationship marketing strategy implemented by the Ramaya Department Store. The method used is a qualitative method. The results of the research show that member loyalty programs are less attractive due to lack of promotion and slow customer service response.